2005
DOI: 10.1021/es048925s
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Emission Factors of Fine and Ultrafine Aerosol Particles for Different Traffic Situations in Switzerland

Abstract: Extended field measurements of particle number (size distribution of particle diameters, D, in the range between 18 nm and 10 microm), surface area concentrations, and PM1 and PM10 mass concentrations were performed in Switzerland to determine traffic emissions using a comprehensive set of instruments. Measurements took place at roads with representative traffic regimes: at the kerbside of a motorway (120 km h(-1)), a highway (80-100 km h(-1)), and in an urban area with stop-and-go traffic (0-50 km h(-1)) regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
59
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(66 citation statements)
references
References 35 publications
(42 reference statements)
5
59
1
1
Order By: Relevance
“…Using particle size classes from 30-10,000 nm and 3-3000 nm Corsmeier et al (2005) and Ban-Weiss et al (2010) found comparable results with around 85% and 88% lower EF for LDV compared to the HDV. In other studies much higher differences between LDV and HDV emission factors were detected, ranging from a factor 10 by Imhof et al (2005) up to a factor 149 by Birmili et al (2009).…”
Section: Emission Factorsmentioning
confidence: 69%
See 2 more Smart Citations
“…Using particle size classes from 30-10,000 nm and 3-3000 nm Corsmeier et al (2005) and Ban-Weiss et al (2010) found comparable results with around 85% and 88% lower EF for LDV compared to the HDV. In other studies much higher differences between LDV and HDV emission factors were detected, ranging from a factor 10 by Imhof et al (2005) up to a factor 149 by Birmili et al (2009).…”
Section: Emission Factorsmentioning
confidence: 69%
“…If the emission factor for a similar size range as in this study is calculated, based on e.g., data provided by Imhof et al (2005) for the size range 18-300 nm, their emission factor was only a factor two higher. In contrast, Corsmeier et al (2005) detected lower emission factor for both HDV and LDV by using instruments which started at particle sizes > 30 nm.…”
Section: Emission Factorsmentioning
confidence: 90%
See 1 more Smart Citation
“…According to Imhof et al (2005a); Janhäll et al (2004); Ketzel et al (2004) and Wåhlin et al (2001) the size distributions measured at the roadside were dominated by nucleation mode particles with a relatively constant peak size of 20 nm. In laboratory and chase measurements the nucleation mode existence and peak diameter show great variation (Kittelson et al, 2004;Vaaraslahti et al, 2004;Rönkkö et al, 2006).…”
mentioning
confidence: 99%
“…This can be explained by ~40% higher driving speed at T4w-nb than those at TI4w-wb while average driving speed at both three-way TIs was almost equal (Table 7). Particle number emission increases with the increase in driving speed due to higher engine load (Imhof et al, 2005;Kumar et al, 2011;Wang et al, 2010 of ZoI depends predominantly on idling time while average PNCs depends on driving speed of the road vehicles. Table 6.…”
Section: Type Of Tismentioning
confidence: 99%